Thermoeconomic analysis of recuperative sub- and transcritical organic Rankine cycle systems - Oyewunmi,OA; Lecompte,S; De,Paepe M; Markides,CN (Elsevier, 2017)
There is significant interest in the deployment of organic Rankine cycle (ORC) technology for waste-heat recovery and power generation in industrial settings. This study considers ORC systems optimized for maximum power generation using a case study of an exhaust flue-gas stream at a temperature of 380°C as the heat source, covering over 35 working fluids and also considering the option of featuring a recuperator. Systems based on transcritical cycles are found to deliver higher power outputs than subcritical ones, with optimal evaporation pressures that are 4-5 times the critical pressures of refrigerants and light hydrocarbons, and 1-2 times those of siloxanes and heavy hydrocarbons. For maximum power production, a recuperator is necessary for ORC systems with constraints imposed on their evaporation and condensation pressures. This includes, for example, limiting the minimum condensation pressure to atmospheric pressure to prevent sub-atmospheric operation of this component, as is the case when employing heavy hydrocarbon and siloxane working fluids. For scenarios where such operating constraints are relaxed, the optimal cycles do not feature a recuperator, with some systems showing more than three times the generated power than with this component, albeit at higher investment costs.